EXCLUSIVE BREASTFEEDING AND COMPLEMENTARY FEEDING HISTORIES IN STUNTING AMONG CHILDREN AGED 24–59 MONTHS AT POSYANDU SIRSAK - Adi Jayanti, Maya Rosvita; Santi, Mina Yumei; Djanah, Nur (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Background: Sleman Regency has a high prevalence of stunted toddlers because it is still above the national target of 14%. Objective: To determine the relationship between the history of exclusive breastfeeding and complementary feeding with the incidence of stunting in toddlers aged 24-59 months at Posyandu Sirsak. Method: The type of this research is observational analytic with a cross-sectional design. The sample consisted of 30 individuals, employing a total sampling technique. Results: There is a relationship between the history of exclusive breastfeeding with a p-value of 0.026 and the history of complementary feeding with a p-value of 0.025 with the incidence of stunting. There is no relationship between maternal age (p-value 0.443), education level (p-value 0.228), employment status (p-value 0.427), low birth weight (p-value 1.000), and family income (p-value 0.665) with the incidence of stunting. The research results indicate that the history of providing complementary feeding is more significantly statistically related than the history of exclusive breastfeeding in children aged 24-59 months, marked by a p-value of 0.038. Conclusion: A relationship exists between the history of exclusive breastfeeding and complementary feeding and the incidence of stunting, where the history of complementary feeding is more significantly statistically related to stunting.